Fetal echocardiography in the 3rd trimester of pregnancy as an essential element of modern prenatal diagnostics and perinatal care – recommendations of Polish Society of Prenatal Cardiology 2020 - Sokołowski, Łukasz; Słodki, Maciej; Murlewska, Julia; Strzelecka, Iwona; Kordjalik, Paulina; Blitek, Marek; Węgrzynowski, Jerzy; Grzesiak, Mariusz; Krekora, Michał; Czajkowski, Krzysztof; Preis, Krzysztof; Respondek-Liberska, Maria (Prenatal Cardiology, 2020)
The purpose of this article is to show that fetal echocardiography should also be performed in the third trimester of pregnancy, both in normal and complicated pregnancies. The article presents a review of the current literature presenting the possibilities and goals of fetal echocardiography in the third trimester of pregnancy in situ ations such as: coarctation of the aorta, premature constriction of the ductus arteriosus, increased fetal lung vascular resistance, hypoplastic left heart syndrome, dextro-transposition of the great arteries, fetal growth restriction, pregestational diabetes mellitus, and gestational diabetes mellitus. A specific feature of fetal echocardiography in the third trimester is the emphasis on the assessment of fetal heart function; therefore, the article describes the current method of assessing it.